Bacterial and mammalian cells adhesion to tantalum‐decorated micro‐/nano‐structured titanium. Issue 3 (2nd December 2016) - Zhu, Yu; Gu, Yingxin; Qiao, Shichong; Zhou, Linyi; Shi, Junyu; Lai, Hongchang
Abstract: Microorganisms are frequently introduced to dental implants during surgery and start the race for the surface with host cells before osseointegration occurs. The aim of the study was to endow implant surfaces with biological functions that reliably select cells over microbes. Nano‐structured tantalum (Ta) has exhibited excellent compatibility. Thus, nano‐structured Ta films were deposited on the sand‐blasted, large grit, and acid‐etched (SLA) titanium by the magnetron sputtering method, thus forming hierarchical micro‐/nano‐structured surfaces. No obvious Ta release confirmed the robustness of the deposited layer probably arising from the stable Ta2 O5 . Moreover, Ta‐modified surfaces not only improved the initial adhesion and spreading of rat bone mesenchymal stem cells (rBMSCs), but also exhibited good antibacterial activities towards Streptococcus mutans and Porphyromonas gingivalis . The satisfactory cell‐surface interactions on Ta‐modified surfaces depended largely on the up‐regulation of adhesion‐related genes and activation of focal adhesion kinase (FAK), as confirmed by real‐time PCR and Western blot. Here, the coculture model was also forwarded to mimic the perioperative bacterial contamination. We found that the adherent cell number and the cell‐surface coverage were hampered by bacteria presence on both surfaces. Yet, rBMSCs still attached and spread more readily on Ta‐modified surfaces than on SLA titanium surfaces even in coculture with adhering oral pathogens. Our results revealed that Ta‐modified micro‐/nano‐structured surfaces would selectively promote cell‐surface rather than bacteria‐surface interactions, boding well for the applications for dental implants in possibly infected environments. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 105A: 871–878, 2017.